Penyelesaian Sengketa Perceraian melalui Mediasi: Studi Efektivitas berdasarkan Tingkat Keberhasilan Pengadilan Agama Metro Kelas 1A - Agus Setiawan (CV. Creative Tugu Pena, 2024)
This research evaluates the effectiveness of mediation in resolving divorce disputes in Class 1A Metro Religious Courts, with the main focus on the success rate of mediation. The aim of this study is to identify how effective mediation is in resolving divorce disputes and analyze the factors that influence the level of success. This research methodology includes quantitative data analysis from mediation cases that have been completed over a certain period. This type of research is sociological empirical legal research (Non-Doctrinal) which is a type of legal research that focuses attention on the reality of law in society or functions to see law in real terms and examine how law is in society (Law In Action). Based on the research results, it was concluded that the effectiveness of the mediation process in resolving case study divorce disputes at the Class 1A Metro Religious Court in terms of increasing the number or success of cases was effective as shown by the success rate of mediation if the percentage was 87.2% of talak divorce cases and 86.5% divorce case. However, from the interview results, the level of success of mediation still has notes related to mediation, namely public awareness regarding the mediation process, facilities and equipment, as well as the importance of the presence of law enforcement. Furthermore, this study can be a reference for Class 1A Metro Religious Courts to increase the effectiveness of mediation by strengthening socialization, providing incentives to mediators, and expanding counseling and guidance to prospective marriage couples through the Ministry of Religion and BP4, in order to reduce the divorce rate.